Ag@Au Core‐Shell Nanowires for Nearly 100 % CO2‐to‐CO Electroreduction. Issue 3 (27th December 2019) - Liu, Jinze; Wang, Yating; Jiang, Hao; Jiang, Haibo; Zhou, Xiaodong; Li, Yuhang; Li, Chunzhong
Abstract: Electrochemical reduction of carbon dioxide (CO2 ) to CO is regarded as an efficient method to utilize the greenhouse gas CO2, because the CO product can be further converted into high value‐added chemicals via the Fisher–Tropsch process. Among all electrocatalysts used for CO2 ‐to‐CO reduction, Au‐based catalysts have been demonstrated to possess high selectivity, but their precious price limits their future large‐scale applications. Thus, simultaneously achieving high selectivity and reasonable price is of great importance for the development of Au‐based catalysts. Here, we report Ag@Au core–shell nanowires as electrocatalyst for CO2 reduction, in which a nanometer‐thick Au film is uniformly deposited on the core Ag nanowire. Importantly, the Ag@Au catalyst with a relative low Au content can drive CO generation with nearly 100 % Faraday efficiency in 0.1 m KCl electrolyte at an overpotential of ca. −1.0 V. This high selectivity of CO2 reduction could be attributed to a suitable adsorption strength for the key intermediate on Au film together with the synergistic effects between the Au shell and Ag core and the strong interaction between CO2 and Cl − ions in the electrolyte, which may further pave the way for the development of high‐efficiency electrocatalysts for CO2 reduction. Abstract : Ag@Au nanowires with a core–shell morphology exhibit a good electrochemical activity with nearly 100 % CO Faraday efficiency for 12 hours.